Steric exclusion and constraint satisfaction in multi-scale coarse-grained simulations. (October 2016) - Taylor, William R.
Abstract : Graphical abstract: Abstract : Highlights: The method developed here provides a fast and flexible way to capture the structure of most macromolecules in a hierarchy of increasingly larger coarse-grained levels without losing the detailed low-level representation. Molecules can then be viewed using an integral graphical viewer or animated through a high-level application programming interface (API) in C++. Although much testing remains to be done, the system has the potential to be applied to very large dynamic systems including both protein and nucleic acids. Abstract: An algorithm is described for the interaction of a hierarchy of objects that seeks to circumvent a fundamental problem in coarse-grained modelling which is the loss of fine detail when components become bundled together. A "currants-in-jelly" model is developed that provides a flexible approach in which the contribution of the soft high-level objects (jelly-like) are employed to protect the underlying atomic structure (currants), while still allowing them to interact. Idealised chains were used to establish the parameters to achieve this degree of interaction over a hierarchy spanning four levels and in a more realistic example, the distortion experienced by a protein domain structure during collision was measured and the parameters refined. This model of steric repulsion was then combined with sets of predicted distance constraints, derived from correlated mutation analysis. Firstly, an integral trans-membrane protein was modelled in which the packing of the seven helices was refined but without topological rearrangement. Secondly, an RNA structure was 'folded' under the predicted constraints, starting only from its 2-dimensional secondary structure prediction.